A 3-min weighted vests re-warmups induce sprint performance enhancements at the start of the second half of a soccer match-play - Ltifi, Mohamed Amine; Turki, Olfa; Racil, Ghazi; Larion, Alin; Chelly, Mohamed Souhaiel; Ben Saad, Helmi; Khalifa, Riadh; Chamari, Karim; Padulo, Johnny (Frontiers in Physiology, 2023)
Purpose: This study aimed to investigate the effect of re-warm-up (RWUP) activities consisting of three sets of 15-m sprints with weighted vests on 20-m sprint performance after the break. Methods: Using a randomized, and counterbalanced cross-over design, twenty U15 elite soccer players performed four RWUP trials which consisted of 15-min of passive rest (control: CONT), 3 × 15-m sprint (RW0%), sprinting with a vest-loaded at 5% of body-mass (BM) (RW5%), sprinting with a 10% BM vest (RW10%). The 3-min RWUP protocols started 10-min after the commencement of the 15-min between-halves break and concluded 2-min before its end. During each testing session, the participant’s RPE scores, and 20-m sprint performance were registered before the first half, and at the end of the break of the simulated match-play. Results: Significant time effects [F (1.72) = 54.37, d = 1.88, p < 0.001; F (1.72) = 9.07, d = 0.77, p = 0.003], and condition effects [F (3.72) = 11.81, d = 1.53, p < 0.001; F (3.72) = 7.36, d = 1.21, p = 0.003] were observed for RPE scores and 20-m sprint performance, respectively. Significant condition-by-time interactions were found for RPE scores (p < 0.003, d = 0.54), and 20-m sprint performance (p < 0.002, d = 0.70). Contrast analysis showed significantly higher RPE scores (p < 0.001, d = 1.55), and improved 20-m sprint performance (p = 0.0004, d = 1.19) in the RW10% condition compared to all other conditions. Conclusion: Sprinting for 3-min with a 10% body-mass vest resulted in the highest RPE scores and the most substantial enhancements in 20-m sprint performance. Young elite soccer players should incorporate 10% body-mass weighted vests in their re-warm-ups to boost post-break sprint performance.